Assessing the impact of the COVID-19 pandemic on recognition and testimony memory: differential effects in young and older adults - Bonilla, Matias; Flores Kanter, Pablo E.; Vidal, Vanessa; Jiménez, Zahira A.; Leon, Candela S.; Urreta Benitez, Facundo A.; Brusco, Luis I.; Vázquez Chenlo, Aylin; Corfdir, Yohann; García Bauza, Cristian; Forcato, Cecilia (Frontiers in Psychology, 2025)
The COVID-19 pandemic negatively impacted global mental health, with younger adults showing higher levels of anxiety and depression than older adults. Given the strong association between emotional states, sleep quality, and memory, the pandemic provided a unique context to investigate how stress influences episodic memory across age groups. We hypothesized that the typical memory advantage of younger adults would be diminished, or even reversed, relative to the performance of older adults on different memory tasks. A total of 159 participants from Buenos Aires were recruited and divided into independent samples. Younger adults during the pandemic (n = 42, M = 16.93, SD = 1.85) and post-pandemic (n = 38, M = 17.31, SD = 1.74), and older adults during the pandemic (n = 41, M = 71.36, SD = 4.84) and post-pandemic (n = 38, M = 65.38, SD = 4.03). In two online sessions, participants completed questionnaires on anxiety, depression, and sleep, watched an aversive video, and performed free recall, facial recognition, and chronological order tasks. Free recall reports were further examined with semantic network measures. Results showed that younger adults reported higher anxiety and depression than older adults, with anxiety decreasing only post-pandemic (p < 0.001). During the pandemic, older adults recalled more episodic details than younger adults (p < 0.01); however, contrary to our expectations, post-pandemic the typical pattern was not restored, as younger adults performed at the same level as older adults on this task. Younger adults performed better than older adults in recalling gist details, defined as a predefined set of central elements from the event, post-pandemic (p < 0.01), and consistently showed better facial recognition across both periods (p < 0.05). Semantic networks were more modular in older adults (p < 0.001), while younger adults’ networks became more efficient post-pandemic. These findings suggest that pandemic stress temporarily reversed age-related memory patterns.